Promoting Student Perspective on English Literature Student Through Alliteration and Assonance Harry Potter of The Goblet Fire - Cindy Andryanti; Evanda Dewi Aisyah; Wahyu Indah Mala Rohmana (LINGUISTICA, 2025)
This study aims to explore how English Literature students understand and interpret the use of alliteration and assonance in the film Harry Potter and the Goblet of Fire. This study uses a descriptive qualitative method to analyze how students interpret these phonetic patterns in the movie, and how this affects their emotional responses and intellectual understanding of the film. The analysis highlights how these literary devices contribute to the style and emotional resonance of the movie's dialogue. This analysis underscores the impact of sound devices in literary and cinematic works, enriching the narrative and enhancing audience engagemen. In addition, this analysis emphasizes how filmmakers strategically use language to achieve various effects such as comedy, elegance, grandeur, and rhythm.